2017
DOI: 10.24953/turkjped.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart defects in Williams syndrome

Abstract: Williams syndrome (WS), also known as Williams-Beuren syndrome, is a rare genetic disorder involving multiple systems including the circulatory system. However, the etiologies of the associated congenital heart defects in WS patients have not been sufficiently elucidated and represent therapeutic challenges. The typical congenital heart defects in WS were supravalvar aortic stenosis, pulmonary stenosis (both valvular and peripheral), aortic coarctation and mitral valvar prolapse. The atypical cardiovascular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
(62 reference statements)
1
25
0
3
Order By: Relevance
“…Case 10 revealed Williams-Beuren syndrome, a well-defined multisystem disorder that is caused by a chromosome 7q11.23 deletion. As previously described, congenital cardiovascular defects are the most clinically significant in 80% of patients with Williams-Beuren syndrome, which is caused by haplo insufficiency in the elastin (ELN) [ 23 , 24 ]. The ultrasound feature of case 10 was CoA and FGR, which was also reported in a study by Yuan et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Case 10 revealed Williams-Beuren syndrome, a well-defined multisystem disorder that is caused by a chromosome 7q11.23 deletion. As previously described, congenital cardiovascular defects are the most clinically significant in 80% of patients with Williams-Beuren syndrome, which is caused by haplo insufficiency in the elastin (ELN) [ 23 , 24 ]. The ultrasound feature of case 10 was CoA and FGR, which was also reported in a study by Yuan et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAs are responsible for more than 50% of spontaneous abortions 2 . Many studies have demonstrated the epidemiology of CA in groups with spontaneous abortions and specific congenital malformations 2–4 . Sezin Yakut showed that cytogenetic abnormalities were detected in 127 of 382 spontaneous abortion cases (33.24%) and that autosomal trisomies were the predominant CA, with a frequency of 48.8% 5 .…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] WS with cardiovascular abnormalities is diagnosed at an average age of 6.2 years. [11] In our patient, she was hospitalized due to hypoxic symptoms at the age of 10 days. At that age, the elfin facial appearance typical of WS had not become evident.…”
Section: Resultsmentioning
confidence: 99%